RELEVANSI PERGESERAN ALIH GUNA LAHAN PERTANIAN MENJADI PEMUKIMAN DI DESA SIMOGIRANG KECAMATAN PRAMBON SIDOARJO (Jurnal Ekonomi Bisnis dan Akuntansi, 2021)
The purpose of this research is to find out how relevant it is related to the conversion of agricultural land use into community settlements and to see how the direct relationship if the conversion of agricultural land to non-agricultural land use continues. And what are the impacts that arise due to a shift in agricultural land which is increasingly narrowing due to the construction of settlements on this agricultural land. The research method used in this study is a qualitative descriptive method. Based on the analysis carried out, the research results obtained that there is a direct relevance to the shift in the use of agricultural land into residential areas, either in the form of development or land clearing. This relevance occurs because with the conversion of agricultural land to non-agriculture in the form of a shift in its actual function to housing, the area of ​​agricultural land becomes increasingly narrow. The availability of increasingly narrow rice fields can have a significant impact, both negative and positive. Keywords: Conversion of agricultural land, Settlement Keywords: Development, Infrastructure, Welfare of the Trucuk Community